2014
DOI: 10.1007/s10557-014-6558-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Dabigatran and Rivaroxaban Compared with Warfarin for Stroke Prevention in Patients with Atrial Fibrillation

Abstract: Rivaroxaban may be a cost-effective alternative to warfarin for the prevention of stroke in patients with AF in Singapore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…The rationale for this was supported by the data from the pivotal trials of edoxaban (Daiichi Sankyo, data on file, 2013) 21 and rivaroxaban, 30 which showed that their relative efficacy versus warfarin did not differ by CHADS 2 score, so there was no need to stratify the thrombotic event risks by CHADS 2 score ( Table 1 ). Consistent with the approach taken by other published cost-effectiveness analyses, the risk of ischemic stroke, TIA, MI, and bleeding events (including hemorrhagic stroke) in our model increased with age, using factors of 1.40, 33 – 36 1.73, 37 1.30, 31 , 32 , 34 , 38 , 39 and 1.97, 31 , 32 , 34 , 36 , 40 respectively, for each decade increase in age. The distribution of stroke severity was based on data from ENGAGE AF-TIMI 48 (Daiichi Sankyo, data on file, 2013).…”
Section: Methodssupporting
confidence: 84%
“…The rationale for this was supported by the data from the pivotal trials of edoxaban (Daiichi Sankyo, data on file, 2013) 21 and rivaroxaban, 30 which showed that their relative efficacy versus warfarin did not differ by CHADS 2 score, so there was no need to stratify the thrombotic event risks by CHADS 2 score ( Table 1 ). Consistent with the approach taken by other published cost-effectiveness analyses, the risk of ischemic stroke, TIA, MI, and bleeding events (including hemorrhagic stroke) in our model increased with age, using factors of 1.40, 33 – 36 1.73, 37 1.30, 31 , 32 , 34 , 38 , 39 and 1.97, 31 , 32 , 34 , 36 , 40 respectively, for each decade increase in age. The distribution of stroke severity was based on data from ENGAGE AF-TIMI 48 (Daiichi Sankyo, data on file, 2013).…”
Section: Methodssupporting
confidence: 84%
“…Moreover, rivaroxaban was consistently reported as a cost-effective alternative to warfarin among AF populations in recent publications [ 15 , 16 , 33 , 35 ]. Rivaroxaban was also shown to be cost-effective compared to warfarin in a Singapore health care setting, which suggests that the cost-effectiveness of rivaroxaban versus warfarin is global [ 36 ]. To be cost-effective means that the new product provides sufficient benefits to justify the added cost.…”
Section: Discussionmentioning
confidence: 99%
“…The only exception was for the analysis for the Greek setting where the total lifetime cost was found lower for rivaroxaban treatment resulting in a cost saving of e239 17 . The number of QALY was found higher for the rivaroxaban treatment compared to the warfarin treatment [8][9][10][11][12][13][14][15][16][17] . Rivaroxaban treatment was found to be cost-effective compared to the warfarin treatment in those studies [8][9][10][11][12][13][14][15][16][17] .…”
Section: Discussionmentioning
confidence: 89%
“…It also has less drug-drug and drug-food interactions than warfarin. Although previous analyses in other countries indicated that rivaroxaban is more cost-effective compared to warfarin [8][9][10][11][12][13][14][15][16][17] . Clinical practices in Japan such as lower anticoagulation targets, healthcare costs and efficacy and safety of rivaroxaban in the Japanese population are different from other countries.…”
Section: Introductionmentioning
confidence: 93%